2015
DOI: 10.1038/jid.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response to Skin Trauma Is Dependent on the Etiology of Injury in a Mouse Model of Burn and Excision

Abstract: Skin trauma has many different causes including incision, blunt force, and burn. All of these traumas trigger an immune response. However, it is currently unclear whether the immune response is specific to the etiology of the injury. This study was established to determine whether the immune response to excision and burn injury of equivalent extent was the same. Using a mouse model of a full-thickness 19 mm diameter excision or 19 mm diameter full-thickness burn injury, we examined the innate immune response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 54 publications
3
58
0
Order By: Relevance
“…Advances in medical management in recent years have resulted in significant declines in hospital mortality,[5, 6]. However, population-based research has shown burn survivors experience decreased long-term survival [7, 8], whilst increased long-term morbidity has been shown both in population studies and other models of burn injury [911]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in medical management in recent years have resulted in significant declines in hospital mortality,[5, 6]. However, population-based research has shown burn survivors experience decreased long-term survival [7, 8], whilst increased long-term morbidity has been shown both in population studies and other models of burn injury [911]. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have shown that the etiology of injury is important, with even non-severe burn injury leading to sustained and unique changes in immune cell profiles in a murine model [11]. However, the consequences of these changes on morbidity in the longer term are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our major findings included a significant loss of the blood lymphocytes and splenic T cells following burn injury and associated sepsis. Studies from other laboratories have also shown that cutaneous causes a suppression of splenic T cell cytokine production (3). Burn injury has also been shown to induce T cell apoptosis (4), a decreased ability of T cells to proliferate upon polyclonal and antigen specific stimulation, and to secrete Th1 cytokines, including interferon-γ (5).…”
Section: Introductionmentioning
confidence: 99%
“…8,13 Despite the absence of a hypermetabolic response, minor burns elicit a substantial acute inflammatory response. 9 It may be that this response in part mediates the profound long-term changes observed after minor burn injuries. 8 Although the incidence rate of admissions was elevated after severe burns, the lack of a significant association may be related to the small numbers of patients with severe burns in this patient cohort, the classification of TBSA used (,20% and $20%), and, potentially, that survivors of severe burns in this study represent a healthier patient subcohort.…”
Section: Figurementioning
confidence: 99%
“…2,5,7,8 These changes have been postulated to be mediated by the acute inflammatory response. 9 Understanding the long-term health effects of burns is of particular importance to young children, who have the highest incidence of burn injuries 10 and the longest time to be affected by any secondary pathology subsequent to burn injury. To date, limited data have been available to examine the long-term health effects of pediatric burns beyond 3 years postburn.…”
Section: What's Known On This Subjectmentioning
confidence: 99%